3 Integration of ISO 45001:2018 Clausula with OHS Criteria and Gap Analysis Criteria 1.1 – 1.2 OHS In PT. X Pasuruan - Khanza Furtina, Nabilah; Widajati, Noeroel (Rifa'Institute, 2023)
Introduction: Based on ILO data, 2018 shows that every year 13.7% workers die as a result of accidents or diseases, even though employee is one of the most important human capital assets in company. Occupational Health and Safety (OHS) Factors managed with applicable regulations. ISO 45001 is an International Standard that regulates the requirements for the OHS Management System. In Indonesia we called it OHS. All sub-systems OHS aim to prevent any unwanted incidents. Objective: To determine integration between ISO 45001:2018 and OHS clauses and determine analysis regarding application of OHS on criteria 1.1 and 1.2 at PT. X. Method: Research method uses qualitative research with a gap analysis approach. Result and Discussion: The research results show that ISO 45001:2018 clause that most relevant to the OHS criteria is clause 8 with 16 equal clauses, while least relevant clause is clause 4 with 1 equal clause. As for the results of gap analysis for application of criterion 1.1 at PT.X 60% do not require CAPA while the application of criteria 1.2 80% does not require CAPA. Conclusion: Not all clauses of ISO 45001:2018 and OHS criteria can be integrated. Application of OHS criteria 1.1 and 1.2 at PT. X is good.